Substitution of anticonvulsant drugs - Bernhard J Steinhoff; Uwe Runge; Otto W Witte; Hermann Stefan; et al (Dove Medical Press, 2009)
Bernhard J Steinhoff1, Uwe Runge2, Otto W Witte3, Hermann Stefan4, Andreas Hufnagel5, Thomas Mayer6, Günter Krämer71Epilepsy Center, Kehl-Kork, Germany; 2Department of Neurology, University of Greifswald, Greifswald, Germany; 3Department of Neurology, University of Jena, Jena, Germany; 4Epilepsy Center, University of Erlangen, Erlangen, Germany; 5Neurocenter, Düsseldorf, Germany; 6Epilepsy Center, Radeberg, Germany; 7Swiss Epilepsy Center, Zurich, SwitzerlandAbstract: Changing from branded drugs to generic alternatives, or between different generic formulations, is common practice aiming at reducing health care costs. It has been suggested that antiepileptic drugs (AEDs) should be exempt from substitution because of the potential negative consequences of adverse events and breakthrough seizures. Controlled data are lacking on the risk of substitution. However, retrospective data from large medical claims databases suggest that switching might be associated with increased use of AED and non-AED medications, and health care resources (including hospitalization). In addition, some anecdotal evidence from patients and health care providers’ surveys suggest a potentially negative impact of substitution. Well-controlled data are needed to assess the real risk associated with substitution, allowing health care professionals involved in the care of patients with epilepsy to make informed decisions. This paper reviews currently available literature, based on which the authors suggest that the decision to substitute should be made on an individual basis by the physician and an informed patient. Unendorsed or undisclosed substitution at the pharmacy level should be discouraged.Keywords: anticonvulsant drugs, epilepsy, generic drugs